Long tail balloon as a new approach for fetoscopic tracheal occlusion for a treatment of severe congenital diaphragmatic hernia. Issue 3 (17th January 2019) - Tchirikov, Michael; Springer, Carsten; Seeger, Sven; Behrmann, Curd; Bergner, Michael; Haase, Roland
Abstract: Severe congenital diaphragmatic hernia (CDH) remains a significant challenge for neonatal specialists. In order to reduce complications during extraction of the surgical balloon after fetoscopic tracheal occlusion (FETO) CDH, we have developed a FETO with a 'long tail balloon' of 2.5 mL volume. Here we describe two successful uses of the device with observed/expected total fetal lung volume (o/e TFLV) of 15% and with o/e TFLV of 24% and 'liver up'. The o/e TFLV increased to 134% in first case and to 47% in second fetus. The balloon was successfully extracted at 34 weeks' gestation by pulling the long tail suture during second fetoscopy. In the second case the fetus pulled out the balloon from trachea itself by traction onto the balloon's long tail. Both neonates were operated on for their CDH with a good outcome. This work showed the feasibility of this long tail balloon for FETO to reduce the technical difficulty of the balloon extraction and the possibility that fetuses are able to extract the balloon by itself by pulling the balloons' long tail. Further development of long tail balloon for FETO could facilitate its extraction thereby reducing neonatal complications.